2022
DOI: 10.3390/healthcare10010144
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Daily Heart Rate Variability Fluctuations Are Associated with Longitudinal Changes in Stress and Somatisation in Police Officers

Abstract: The emergence of wearable sensors that allow for unobtrusive monitoring of physiological and behavioural patterns introduces new opportunities to study the impact of stress in a real-world context. This study explores to what extent within-subject trends in daily Heart Rate Variability (HRV) and daily HRV fluctuations are associated with longitudinal changes in stress, depression, anxiety, and somatisation. Nine Dutch police officers collected daily nocturnal HRV data using an Oura ring during 15–55 weeks. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…One study specifically focused on anxiety and found a positive relationship between the LF/HF ratio and anxiety based on self-assessments using the State-Trait Anxiety Scale [ 50 ]. HR [ 34 , 35 ] and RMSDD increase during stress [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study specifically focused on anxiety and found a positive relationship between the LF/HF ratio and anxiety based on self-assessments using the State-Trait Anxiety Scale [ 50 ]. HR [ 34 , 35 ] and RMSDD increase during stress [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…HR was elevated when participants were stressed, and PPG could accurately capture these physiological changes, including HR reduction during relaxing exercises [ 10 , 42 , 43 , 64 , 65 ]. In addition to stress, PPG also accurately detects patients who are depressed [ 32 - 34 , 37 , 38 , 40 , 41 , 44 , 45 , 48 , 49 , 52 , 54 ], including those with MDD. In other words, depression was associated with a lower HR in contrast to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyzed participants all scored relatively well on the mental well-being questionnaires ( Table 1 ). Another article that was based on data from this same study population showed that some participants reported moderately elevated stress and somatization throughout the study period, but that there were no clinically relevant signs of anxiety and depression [ 41 ]. Future studies with a more mentally challenged sample need to verify the current findings for more challenging conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected for two purposes: (1) comparing longitudinal (5-week) trends in daily resting HRV and fluctuations therein to full questionnaire outcomes for stress, somatization, anxiety, and depression, and (2) the assessment of potential bidirectional and/or multi-day associations of sleep and resting HRV with stress-related EMA outcomes. The results of the former are published elsewhere [ 41 ], whereas the results of the latter are presented in this paper. The study protocol was approved by the ethical committee of the Hanze University of Applied Sciences Groningen (heac.2020.012).…”
Section: Methodsmentioning
confidence: 99%